Alterations of spatiotemporal and ground reaction force variables during decelerated sprinting - Nagahara, R.; Girard, O. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study aimed to elucidate changes in spatiotemporal and ground reaction force (GRF) variables during 90-m overground decelerated sprinting and determinants of the decrease in running speed. In 14 sub-elite male sprinters, a virtual 90-m sprint was reconstructed during which spatiotemporal and GRF variables were averaged for four steps in maximal speed (45.8-m mark) and deceleration (76.5-m mark) phases. With decreases in running speed (3.5 ± 1.1%) from the maximal speed to deceleration phases, step frequency (SF) (3.5 ± 1.9%), net anteroposterior mean force (64.4 ± 15.9%), and propulsive and vertical mean forces during the propulsive phase (3.5 ± 3.8% and 5.3 ± 3.3%) decreased, and support (ST) (2.9 ± 2.5%) and flight times (FT) (4.3 ± 3.3%), braking mean force (7.3 ± 4.0%), and effective vertical impulse during the entire support (5.1 ± 3.4%) and braking phases (20.6 ± 11.2%) increased. In addition, the decrease in running speed was associated with changes in SF, ST, and net anteroposterior mean force (r = .667, -.713, and .524, respectively). The current results demonstrate that decreases in running speed during short-distance overground sprinting are probably caused by decreases in SF through increases in ST and FT, as well as impairment of the ability to minimize braking force and maintaining propulsive force. A compromised ability to maintain the magnitude of applied force during the propulsive phase and the necessity for lengthening FT may cause greater braking force, which increases effective vertical impulse during the braking and entire support phases. The SF, ST, and net anteroposterior mean force are determinants of the magnitudes of decreases in running speed during short-distance overground sprinting.